A strategy to enhance the quality of public administration services at better Tadulako University - Munari (The International Journal of Politics and Sociology Research, 2024)
The study aims to explore strategies to enhance public administration capacity at Tadulako University, using a qualitative approach through case studies. This research mainly focuses on understanding how the applied strategies can improve administrative processes and provide better services to students and staff. Researchers collect data by conducting in-depth interviews, live observations, and document analysis with administrative staff, students, and faculty. Researchers conduct thematic analysis to identify key themes and comprehend the effectiveness and impact of implemented strategies. Research results show that integrating information technology, staff training, and revising bureaucratic processes are critical factors in improving the efficiency and quality of administrative services. Data triangulation reinforces these findings, ensuring the validity and reliability of the results. The research provides insights into best organizational practices and offers valuable recommendations for other higher education institutions facing similar challenges. These implications extend beyond operational improvements to enhancing student education experiences, illustrating the connection between effective administration and academic success in higher education institutions.